Synthesis of gold nanospheres and nanotriangles by the Turkevich approach - Shankar, S. S.; Bhargava, S.; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2005)
Gold nanoparticles of triangular morphology possess interesting optical properties with potential application in medicine and infrared absorbing coatings, however, little is known about conditions that favor their growth. In this paper, we have reinvestigated a time-tested recipe for the formation of gold nanospheres by citrate reduction of aqueous gold ions under boiling conditions (Turkevich recipe). Our principle findings are that gold nanotriangle formation is kinetically controlled and is highly favored at low temperatures. Furthermore, the presence of chloride ions from the precursor chloroaurate ions plays a major role in promoting the growth of [111] oriented triangular/truncated triangular particles. The presence of bromide and iodide ions that possess the ability to replace surface-bound chloride ions inhibits triangle formation to varying degrees.
Keywords: Crystal growth; Gold; halides; nanospheres; nanotriangles; Temperature effect

Enhancing intermolecular benzoyl-transfer reactivity in crystals by growing a ``reactive'' metastable polymorph by using a chiral additive - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2009)
Racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate, which normally crystallizes in a monoclinic form (form I, space group P2(1)/n) could be persuaded to crystallize out as a metastable polymorph (form II, space group C2/c) by using a small amount of either D- or L- 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate as an additive in the crystallization medium. The structurally similar enantiomeric additive was chosen by the scrutiny of previous experimental results on the crystallization of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate. Form II crystals call be thermally transformed to form I crystals at about 145 degrees C. The relative organization of the molecules in these dimorphs vary slightly in terms of the helical assembly of molecules, that is, electrophile (El)center dot center dot center dot nucleophile (Nu) and C-H center dot center dot center dot pi interactions, but these minor variations have a profound effect on the facility and specificity of benzoyl-group-transfer reactivity in the two crystal forms. While form II crystals undergo a clean intermolecular benzoyl-group-transfer reaction, form I crystals are less reactive and undergo non-specific benzoyl-group transfer leading to a Mixture of products. The role played by the additive in fine-tuning small changes that are required in the molecular packing opens up the possibility of creating new polymorphs that show varied physical and chemical properties. Crystals of D-2.6-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (additive) did not show facile benzoyl-group-transfer reactivity (in contrast to the corresponding racemic compound) due to the lack of proper juxtaposition and assembly of molecules.
Keywords: Acylation; carbohydrates; Crystal growth; cyclitols; solid-state reactions

Growth of barium oxalate crystals in agar-agar gel and their characterization - Dalai, P. V.; Saraf, K. B.; Shah, S. (Crystal Research and Technology, 2009)
{Single crystals of barium oxalate have been grown by get method using agar-agar gel as media of growth at ambient temperature. The optimum conditions were established by varying various parameters such as concentration of gel, concentration of reactant, gel setting time etc. Prismatic platy shaped transparent crystals were obtained. The grown crystals were characterized through powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) studies, Thermogravimetric (TGA) and Differential thermal analysis (DTA). The compound crystallizes under monoclinic structure with lattice parameters a = 6.6562 angstrom
Keywords: barium oxalate; Crystal growth; FT-IR; TGA/DTA; XRD

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions